Neuroanatomy : an illustrated colour text - Crossman, A.R.; Neary, David (Professor of neurology); Crossman, Ben ([Amsterdam] : Elsevier, 2020)
Offers concise, superbly illustrated coverage of neuroanatomy, that throughout makes clear the relevance of the anatomy to the practice of modern clinical neurology. Building on the success of previous editions, this sixth edition has been fine-tuned to meet the needs of today's medical students - and will also prove invaluable to the range of other students and professionals who need a clear, current understanding of this important area. Generations of readers have come to appreciate the straightforward explanations of complex concepts that students often find difficult, with minimum assumptions made of prior knowledge of the subject.
Introduction and overview -- Cells of the nervous system -- Peripheral nervous system -- Autonomic nervous system -- Coverings of the central nervous system -- Spinal cord -- Brainstem -- Cranial nerves and cranial nerve nuclei -- Cerebellum -- Thalamus -- Cerebral hemisphere and cerebral cortex -- Basal ganglia -- Visual system -- Hypothalamus, limbic system and olfactory system.
Previous edition: Edinburgh: Churchill Livingstone, 2015.
This book includes online access at https://studentconsult.inkling.com/, please refer library staff for the password.
Includes index.
Keywords: Central Nervous System -- anatomy & histology; Atlases